Unanticipated Aggregate Disturbances and Tests of the Life-Cycle Consumption Model Using Panel Data - Mariger, Randall P.; Shaw, Kathryn (The Review of Economics and Statistics, 1993)
Randall P. Mariger, Kathryn Shaw, Unanticipated Aggregate Disturbances and Tests of the Life-Cycle Consumption Model Using Panel Data, The Review of Economics and Statistics, Vol. 75, No. 1 (Feb., 1993), pp. 48-56